KOREKSI SECARA SUBJEKTIF TERHADAP PENDERITA HIPERMETROPIA DI SUPER OPTICAL PADANG - Rina novalinda (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Abstract : This scientific paper discusses the Subjective Correction of Patients with Hypermetropia at Super Optical Padang. This study aims to: (1) Know the refraction procedure in determining the results of subjective corrections in patients with hypermetropia. (2) Knowing the things that affect subjective inaccuracies in hypermetropia. This type of research is quantitative descriptive. The population in this study were all patients who experienced hypermetropic refraction abnormalities during the study. Sampling in this study is the total sampling technique. Data was collected through a questionnaire, then the data were discussed in accordance with the theories proposed in the literature review. The results of the study can be seen that 29 respondents (96.7%) performed refraction procedures in determining the results of subjective corrections and 1 respondent (3.3%) did not carry out refraction procedures in determining the results of corrections subjectively and 11 respondents (36.7%) felt that it had influenced subjective corrective inaccuracy in hypermetropia and 19 respondents (63.3%) did not feel that influenced subjective inaccuracy in hypermetropia. Keywords: Hipermetropia Patients